2022
DOI: 10.1136/jnnp-2021-328331
|View full text |Cite
|
Sign up to set email alerts
|

Fat-rich versus carbohydrate-rich nutrition in ALS: a randomised controlled study

Abstract: ObjectiveThere is growing evidence that the course of amyotrophic lateral sclerosis (ALS) may be influenced beneficially by applying high-caloric food supplements (HCSs). However, it is unknown which composition of nutrients offers optimal tolerability and weight gain.MethodsWe conducted a randomised controlled study (Safety and Tolerability of Ultra-high-caloric Food Supplements in Amyotrophic Lateral Sclerosis (ALS); TOLCAL-ALS study) in 64 patients with possible, probable or definite ALS according to El Esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…The median sample size in the included studies was 56, ranging from 7 to 94. The prevalence of appetite loss in this population, when reported, varied from 18.0% to 53.2% 3,5,9,20,21,25 …”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…The median sample size in the included studies was 56, ranging from 7 to 94. The prevalence of appetite loss in this population, when reported, varied from 18.0% to 53.2% 3,5,9,20,21,25 …”
Section: Resultsmentioning
confidence: 79%
“…After full‐text review, five articles were excluded (Figure 1). The remaining ten articles met the inclusion criteria and were eligible for data synthesis 3,5,9,19–25 . The earliest publication date was 2010, 19 with most articles (n = 7, 70%) published in 2019 or more recently (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it is unclear whether the potential beneficial effects were mainly driven by the high-energy or the high-fat aspect of the intervention, and what the optimal composition of a high-caloric intervention should look like. A recent open-label study in 64 patients over 4 weeks [39] found that a short-term increase of body weight could be achieved by high-fat as well as high-carbohydrate, high-caloric supplements, although the effect was more pronounced in the high-fat groups. It also indicated that high dosages of high-caloric supplements frequently caused gastrointestinal tolerability issues.…”
Section: High-caloric Fat-rich Nutritionmentioning
confidence: 99%